2021
DOI: 10.1002/ppul.25505
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID‐19 lockdown on children with asthma‐related symptoms: A tertiary care center experience

Abstract: Background: Acute asthma exacerbations are a common cause for emergency department (ED) visits and hospitalizations in children. Since the outbreak of coronavirus disease 2019 (COVID-19) and the education system closure/total lockdown in Israel on March 2020, we have noticed a decrease in pediatric ED visits and an increase in hospitalizations of asthma exacerbations.Objective: to examine the patterns of ED visits for asthma exacerbations during COVID-19 outbreak, in comparison to the previous year.Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Areas among them, the exposure to outdoor allergens was probably not significantly reduced, even during the lockdown. 67 A Turkish study reported this effect on house dust mite-sensitized children with respiratory allergies during March to May 2020, a period that included a 75-days lockdown from April 3. 68 Mild to moderate asthmatic children with or without allergic rhinitis (n ¼ 165) (from which 61.8% were sensitized to house dust mites), experienced significantly less upper respiratory tract infections and reduced asthma exacerbations compared with the same period in the previous year.…”
Section: Effect Of Changes In Environmental Allergen Exposures On All...mentioning
confidence: 99%
“…Areas among them, the exposure to outdoor allergens was probably not significantly reduced, even during the lockdown. 67 A Turkish study reported this effect on house dust mite-sensitized children with respiratory allergies during March to May 2020, a period that included a 75-days lockdown from April 3. 68 Mild to moderate asthmatic children with or without allergic rhinitis (n ¼ 165) (from which 61.8% were sensitized to house dust mites), experienced significantly less upper respiratory tract infections and reduced asthma exacerbations compared with the same period in the previous year.…”
Section: Effect Of Changes In Environmental Allergen Exposures On All...mentioning
confidence: 99%
“… 9 Various recent studies from different countries have reported improvement in the control of children with asthma. 5 , 6 , 10 A recently published meta‐analysis reported a significant improvement in the level of asthma control compared to the same period before the COVID‐19 pandemic. Those authors also emphasized that the exact factors leading to these improvements needed to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Real‐life data showing how children with asthma are affected by major changes in living conditions during the Covid‐19 pandemic are limited. 5 , 6 , 7 This study was performed to reveal the effect of the Covid‐19 pandemic and of the social isolation rules imposed on children on asthma symptoms, frequency of exacerbations, and prophylactic drug use, to compare clinical follow‐up and drug use data with the previous year, and to identify the factors causing a difference.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased adherence to controller medications among the asthmatic population during lockdowns was demonstrated. 30,32,33 In the present paper, we aimed to highlight the additional potential role played by the reduced exposure to environmental factors-that is, air pollution and pollen-in this "anomalous" pattern of asthma exacerbations in 2020.…”
Section: Pollenmentioning
confidence: 99%
“…Several studies reported how social distancing and stepped-up hygiene measures determined a concomitant reduction in the diffusion of respiratory pathogens, leading to decreased respiratory tract infections, 3,8,[28][29][30][31][32] and identify it as the main factor. Moreover, increased adherence to controller medications among the asthmatic population during lockdowns was demonstrated.…”
Section: Pollenmentioning
confidence: 99%